Host-Directed Therapies for Cutaneous Leishmaniasis - Novais, Fernanda O.; Amorim, Camila Farias; Scott, Phillip (Frontiers in Immunology, 2021)
Cutaneous leishmaniasis exhibits a wide spectrum of clinical presentations from self-resolving infections to severe chronic disease. Anti-parasitic drugs are often ineffective in the most severe forms of the disease, and in some cases the magnitude of the disease can result from an uncontrolled inflammatory response rather than unrestrained parasite replication. In these patients, host-directed therapies offer a novel approach to improve clinical outcome. Importantly, there are many anti-inflammatory drugs with known safety and efficacy profiles that are currently used for other inflammatory diseases and are readily available to be used for leishmaniasis. However, since leishmaniasis consists of a wide range of clinical entities, mediated by a diverse group of leishmanial species, host-directed therapies will need to be tailored for specific types of leishmaniasis. However, there is now substantial evidence that host-directed therapies are likely to be beneficial beyond autoimmune diseases and cancer and thus should be an important component in the armamentarium to modulate the severity of cutaneous leishmaniasis.